Quantum-Secure Cryptographic Primitives for Embedded ECE Systems - El Manaa Barhoumi; Y. Charabi (Electronics, Communications, and Computing Summit, 2025)
The explosion of quantum computing is a significant threat to classical cryptographic systems especially those that are utilised in embedded Electronics and Communication Engineering (ECE) including internet of things nodes, medical devices, sensor networks and industrial control systems. The cryptographic algorithms that are used as the foundation of present day embedded security infrastructure, such as RSA and ECC, are vulnerable to quantum attacks, namely, Shor and Grover algorithms. As a reaction to this new exposure, this research studies the origin, deployment, and improvement of quantum-safe cryptographic primitives that are specifically constructed to work under the harsh resource limitations of embedded ECE systems. We examine various post quantum cryptographic (PQC) methods, such as lattice-based, hash-based, code based and multivariate polynomial based methods, with an eye on how they carry over to the embedded microcontroller architectures, like ARM Cortex-M and RISC-V. Specifically, we consider some of the NIST recommended candidates: Kyber (composite modular arithmetic-based KEM), Dilithium (composite modular arithmetic-based signature), and SPHINCS+ (hash-based signature) which are implemented with platform-custom optim Experimental analyses show that our optimized implementations can efficiently reduce up to 42 percent of the execution time and up to 30 percent of energy consumption when compared to unoptimized PQC libraries, befitting the content of highly resistant of quantum adversaries and side-channel attacks. The suggested framework is relevant to satisfy the requirements of the NIST Level 1 security, and two typical embedded platforms approve the framework. Furthermore, the paper utilises energy profiling, timing benchmarks and memory usage analysis to give a full picture of the viability of PQC integration. The contribution made is in terms of a simple and deployable, scaleable answer to the budding Post-Quantum Embedded Cryptography by allowing quantum-resilient security of next generation ECE systems, making it viable to implement both secure boot, firmware, and data transfers in insecurely constrained (low storage, low power) settings.